Hannah Hibbs: capstone - Hibbs, Hannah, artist (Colorado State University. Libraries, 2015)
The artist's statement: I have been surrounded by art my entire life - from performance art to fine art. All materials and processes have interested me and I have had the opportunity to experiment with many. Compared to fine art, graphic design adds an intellectual layer. Rather than just communicated a feeling or statement, graphic design can be utilized to communicate the most dry of subject matter. Design is about dissecting information given to you and creating art the effectively tells the viewers what needs to be said. I enjoy the challenge of communicating difficult information successfully to viewers. The daunting task of branding a company that will use your design and logo for years to come is an exciting experience. Designers' work forces them to become knowledgeable on a wide variety of topics. My goals as a graphic designer is to clearly communicate information to viewers.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.